Validated Pediatric Functional Outcomes of All-epiphyseal ACL Reconstructions: Does Reinjury Affect Outcomes?. Issue 4 (April 2020) - Ranade, Sheena C.; Refakis, Christian A.; Cruz, Aristides I.; Leddy, Kelly L.; Wells, Lawrence; Lawrence, John Todd; Ganley, Theodore J.
Abstract : Background: Greater frequency and intensity level of sports participation may be contributing to an increasing incidence of anterior cruciate ligament (ACL) tears in skeletally immature athletes. Prior studies have assessed the functional outcomes of physeal-respecting ACL reconstruction in this patient population based on adult functional outcomes scoring systems; however, there is only sparse literature evaluating functional outcomes of this specific patient population. This study aimed to retrospectively evaluate a cohort of pediatric patients who had undergone all-epiphyseal ACL reconstruction (AEACLR) with a set of clinically validated, pediatric-specific patient-reported functional outcomes scores (PRFOS). We hypothesized that patients who had rerupture would have significantly lower outcomes scores compared with those who did not rerupture. Methods: This was a retrospective evaluation of AEACLR patients at a single, tertiary care, children's hospital within a period of 2 years and had >6 months of initial clinical postoperative follow-up. Those who consented to participation were provided an online combined survey including questions relating to demographics and rerupture as well as 3 validated pediatric PRFOS. Statistical analysis of the cohort demographics, PRFOS, and subgroup analysis of the rerupture group compared with the ACL intact patients was performed. Results: The mean functional outcome scores at a mean of 48.6 months from surgery demonstrated excellent return to functional activity (Mean International Knee Documentation Committee, 93.8; Pedi-Patient-Reported Outcomes Measurement Information System, 98.8; Pedi- Functional Activity Brief Score, 21.6). There was a 13% rerupture rate and rerupture patients had a significantly decreased Pedi-International Knee Documentation Committee (94.9 intact vs. 86.0 rerupture; P =0.001) and Pedi-Patient-Reported Outcomes Measurement Information System (99.4 intact vs. 95.4 rupture; P =0.001) scores. Conclusions: AEACLR patients have excellent outcomes based on pediatric-specific PRFOS. Rerupture patients demonstrated a decrease in functional outcomes scores compared with intact ACL patients. The results demonstrate the efficacy of AEACLR as measured by pediatric-specific functional outcome scores for the treatment of ACL rupture in skeletally immature athletes. Level of Evidence: Level III—retrospective comparative study.